The Ca(++)-channel blocker Ro 40-5967 blocks differently T-type and L-type Ca++ channels - Mehrke, Gerhard; Zong, X. G.; Flockerzi, Veit; Hofmann, Franz (The journal of pharmacology and experimental therapeutics, 1994)
The effects of Ro 40-5967, a nondihydropyridine Ca++ channel blocker, on low-voltage activated (T-type) and high-voltage activated (L-type) Ca++ channels were compared. L-type barium currents were measured in Chinese hamster ovary cells stably transfected with the alpha 1 subunit of the class Cb Ca++ channel. T-type barium currents were investigated in human medullary thyroid carcinoma cells. The Ba++ currents of human medullary thyroid carcinoma cells were transient, activated at a threshold potential of -50 mV with the maximum at -14 +/- 3.2 mV and blocked by micromolar Ni++. The T- and L-type current inactivated with time constants of 33.4 +/- 4.1 and 416 +/- 26 msec at maximum barium currents, respectively. Ro 40-5967 inhibited reversibly the T- and L-type currents with IC50 values of 2.7 and 18.6 microM, respectively. The inhibition of the L-type current was voltage-dependent, whereas that of the T-type current was not. Ro 40-5967 blocked T-type current already at a holding potential of -100 mV. The different types of block, i.e., voltage-dependent vs. tonic block, may contribute to the pharmacological profile of Ro 40-5967 in intact animals.